Perovskite solar cell based on modified SnO2 electron transport layer and room temperature preparation method

CN123021890APending Publication Date: 2026-10-30SOUTHWEAT UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611351443.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-02
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有方法主要聚焦于缺陷钝化,忽视了界面润湿性和成核热力学在决定大气环境下钙钛矿薄膜质量中的关键作用

Benefits of technology

本发明将β-MHCl修饰的SnO2作为电子传输层的埋底界面修饰,利用-SH和-NH3+双官能团的协同效应,一方面通过-SH基团还原钝化SnO2中的氧空位缺陷并提高其导电性,另一方面通过-NH3+与钙钛矿前驱体中的卤素离子形成强氢键相互作用,显著改善钙钛矿前驱体溶液在SnO2表面的润湿性,有效降低异质成核的Gibbs自由能垒,从而在室温大气环境下实现高质量钙钛矿薄膜的可控制备。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123021890A_ABST
    Figure CN123021890A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of solar cells, and discloses a perovskite solar cell based on modified tin dioxide and a room-temperature preparation method. β The perovskite solar cell prepared by the application has a champion photoelectric conversion efficiency of 25.68%, which is one of the highest efficiencies of n-i-p type perovskite solar cells prepared in an atmospheric environment at present, the device still maintains 85.21% of the initial efficiency after 5500 hours of storage, and maintains more than 97% of the initial efficiency after 2000 hours of maximum power point tracking, so that the application has a very high industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solar cell technology, specifically to a perovskite solar cell based on modified tin dioxide and a method for its room temperature fabrication. Background Technology

[0002] Perovskite solar cells (PSCs) have become one of the most promising next-generation photovoltaic technologies due to their excellent photoelectric properties, including high absorption coefficient, long carrier diffusion length, tunable bandgap, and low-cost solution processability. However, most perovskite solar cells currently require inert atmospheres to protect the moisture-sensitive perovskite material from degradation during film formation. These stringent preparation conditions significantly increase manufacturing costs, infrastructure investment, and energy consumption, posing a major obstacle to large-scale industrialization. Therefore, achieving controllable preparation of high-efficiency and stable perovskite solar cells under atmospheric conditions has become a key direction for promoting this technology from the laboratory to industrialization.

[0003] In nip-type perovskite solar cells, the buried interface between the electron transport layer (ETL) and the perovskite light-absorbing layer is a decisive factor in determining the device's efficiency and stability. This buried interface not only determines the initial nucleation and thin film formation of the perovskite but also dominates charge extraction, energy level alignment, and ion migration. Tin dioxide (SnO2) has become the most widely used electron transport material in nip-type perovskite solar cells due to its high electron mobility, suitable band alignment, low-temperature processability, and excellent chemical stability. However, SnO2 films prepared under atmospheric conditions inevitably contain surface defects, including oxygen vacancies (V0.05). O ), uncoordinated Sn 4+ Sites and suspended hydroxyl groups (-OH). These defects not only act as nonradiative recombination centers, disrupting the interfacial energy level arrangement, but more importantly, the traditional SnO2 surface has poor wettability to perovskite precursor solutions, leading to uneven perovskite nucleation, high defect density, and poor crystallinity. These problems are particularly severe in atmospheric processing due to uncontrolled crystallization kinetics.

[0004] To address these issues, researchers have attempted to introduce multifunctional molecular modifiers into the SnO2 / perovskite buried interface, simultaneously passivating defects on both sides of the interface and regulating perovskite crystallization. For example, molecules containing carboxyl groups (-COOH) can interact with uncoordinated Sn... 4+ Site coordination, while amino (-NH2) or guanidine groups can coordinate with Pb in perovskite. 2+ and I - Defect interactions. However, existing methods mainly focus on defect passivation, neglecting the crucial role of interfacial wettability and nucleation thermodynamics in determining the quality of perovskite films under atmospheric conditions. Summary of the Invention

[0005] This invention addresses the problems existing in the prior art by providing a perovskite solar cell based on modified tin dioxide and a method for its room temperature preparation.

[0006] The technical solution adopted in this invention is: a perovskite solar cell based on modified tin dioxide, comprising, from bottom to top, a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, and a hole transport layer; and further comprising a metal counter electrode; The electron transport layer is mercaptoethylamine hydrochloride. β Preparation of SnO2 modified with -MHCl.

[0007] A room-temperature fabrication method for a perovskite solar cell based on modified tin dioxide, comprising the following steps: Step 1: Spin-coating a conductive substrate surface with... β SnO2 colloid of -MHCl was annealed to obtain an electron transport layer. Step 2: Prepare a perovskite light-absorbing layer on the electron transport layer using spin coating, followed by annealing. Step 3: Spin-coat a hole transport layer onto the surface of the perovskite light-absorbing layer obtained in Step 2; Step 4: Deposit a metal counter electrode on the surface of the hole transport layer.

[0008] Furthermore, in the SnO2 colloidal solution β The concentration of -MHCl is 0.25~1.0 mg / mL.

[0009] Furthermore, in step 1, the annealing temperature is 130~170 ℃ and the annealing time is 20~40 min.

[0010] Furthermore, in step 2, the perovskite light-absorbing layer is FA. 0.9 Cs 0.07 MA 0.03 PbI 2.76 Br 0.24 .

[0011] Furthermore, the spin coating process of the perovskite light-absorbing layer in step 2 is as follows: first spin coating at 1000 rpm for 10 s, and then spin coating at 4000 rpm for 30 s.

[0012] Furthermore, in step 2, the annealing temperature is 140~160 ℃ and the annealing time is 20~30 min.

[0013] Furthermore, chlorobenzene, an anti-solvent, is added during the spin coating process in step 2.

[0014] Furthermore, the conductive substrate is fluorine-doped tin oxide (FTO) conductive glass.

[0015] Furthermore, the hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene.

[0016] Furthermore, in step 4, the vacuum evaporation rate is 0.3~0.8 Å / s, and the vacuum degree is 10. -5 ~10 - 6 Pa, with a deposition thickness of 50~100 nm.

[0017] The beneficial effects of this invention are: This invention will β -MHCl-modified SnO2 serves as the buried interface modification for the electron transport layer, utilizing -SH and -NH3. + The synergistic effect of the bifunctional groups, on the one hand, reduces and passivates oxygen vacancy defects in SnO2 and improves its conductivity through the reduction of the -SH group, and on the other hand, it enhances the conductivity through the -NH3 group. + The strong hydrogen bond interaction with halide ions in the perovskite precursor significantly improves the wettability of the perovskite precursor solution on the SnO2 surface and effectively reduces the Gibbs free energy barrier for heterogeneous nucleation, thereby enabling the controllable preparation of high-quality perovskite films at room temperature and in atmospheric conditions.

[0018] The perovskite solar cell prepared by this invention achieves a champion photoelectric conversion efficiency of 25.68%, which is one of the highest efficiencies of nip-type perovskite solar cells prepared under atmospheric conditions. Moreover, the unencapsulated device still retains 85.21% of its initial efficiency after 5500 hours of storage and maintains more than 97% of its initial efficiency after 2000 hours of maximum power point tracking, showing extremely high industrial application prospects. Attached Figure Description

[0019] Figure 1 The JV curves are for the champion perovskite solar cells obtained in Example 1 and the comparative example of this invention.

[0020] Figure 2 The images show the FTIR characterization of the electron transport layer thin film obtained in step 1 of Embodiment 1 and Comparative Example 1 of the present invention.

[0021] Figure 3 The above are XPS Sn 3d high-resolution spectra of the electron transport layer thin films obtained in step 1 of Embodiment 1 and Comparative Example 1 of the present invention.

[0022] Figure 4 The images show the XPS O1s high-resolution spectra of the electron transport layer films obtained in step 1 of Example 1 and Comparative Example 1 of this invention. a is Comparative Example 1, and b is Example 1.

[0023] Figure 5 The contact angles of the perovskite precursor solution on the surface of the electron transport layer film obtained in step 1 of Example 1 and Comparative Example 1 are: a for Comparative Example 1 and b for Example 1.

[0024] Figure 6 The images show a comparison of in-situ crystallization images of the perovskite absorbing layer obtained by fluorescence polarization light microscopy (FPLM) in Example 1 and Comparative Example 1, respectively. a is Comparative Example 1 and b is Example 1.

[0025] Figure 7 The figures show a comparison of the steady-state PL spectrum and TRPL attenuation curve of the perovskite light-absorbing layer in Example 1 and Comparative Example 1 of the present invention. a is the PL spectrum and b is the TRPL attenuation curve.

[0026] Figure 8 These are scanning electron microscope (SEM) images comparing the surface and subsurface morphology of the perovskite light-absorbing layer in Example 1 and Comparative Example 1 of the present invention. a is the SEM image of the surface of Comparative Example 1, b is the SEM image of the surface of Example 1, c is the SEM image of the subsurface interface of Comparative Example 1, and d is the SEM image of the subsurface interface of Example 1.

[0027] Figure 9 This is a comparison chart of the Mott-Schottky curves of the device in Embodiment 1 and the device in Comparative Example 1 of the present invention.

[0028] Figure 10 This is a comparison diagram of the Nyquist impedance spectra of the device in Embodiment 1 and the device in Comparative Example 1 of the present invention.

[0029] Figure 11 This is a schematic diagram comparing the environmental stability of perovskite solar cells obtained in Example 1 and Comparative Example 1 of the present invention.

[0030] Figure 12 This refers to the maximum power point tracking stability of the device in Embodiment 1 of the present invention. Detailed Implementation

[0031] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.

[0032] A perovskite solar cell based on modified tin dioxide includes, from bottom to top, a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, and a hole transport layer; it also includes a metal counter electrode. The electron transport layer is mercaptoethylamine hydrochloride. β Preparation of SnO2 modified with -MHCl.

[0033] A room-temperature fabrication method for a perovskite solar cell based on modified tin dioxide, comprising the following steps: Step 1: Spin-coating a conductive substrate surface with... βSnO2 colloids containing -MHCl, after annealing, yield an electron transport layer; SnO2 colloidal solution β The concentration of -MHCl was 0.25–1.0 mg / mL. The annealing temperature was 130–170 °C, and the annealing time was 20–40 min. The conductive substrate was fluorine-doped tin oxide (FTO) conductive glass.

[0034] Step 2: Prepare a perovskite light-absorbing layer on the electron transport layer using spin coating, followed by annealing. The annealing temperature is 130–170 °C, and the annealing time is 20–40 min. The spin coating process for the perovskite light-absorbing layer involves first spin coating at 1000 rpm for 10 s, then spin coating at 4000 rpm for 30 s. The annealing temperature is 140–160 °C, and the annealing time is 20–30 min. Chlorobenzene, an anti-solvent, is added during the spin coating process.

[0035] MAI, FABr, CsI, PbBr2, FAI, and PbI2 were dissolved in a DMF / DMSO mixed solvent (volume ratio 4:1) at stoichiometric ratios, with NMP added as a coordinating additive. The mixture was stirred at room temperature for 10–14 h. The perovskite precursor solution was filtered through a 0.22 µm PTFE filter. A one-step spin-coating method was used in a glove box to... β A perovskite light-absorbing layer was prepared on an MHCl-SnO2 electron transport layer.

[0036] Step 3: Spin-coat a hole transport layer onto the surface of the perovskite light-absorbing layer obtained in Step 2; the hole transport layer is 2,2',7,7'-tetratetra[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene. Dissolve Spiro-OMeTAD in chlorobenzene (concentration 70~90 mg / mL), add tBP and Li-TFSI acetonitrile solution (concentration 520 mg / mL), and spin-coat the film in a glove box at a speed of 2000~4000 rpm for 20~40 s.

[0037] Step 4: Deposit a metal counter electrode onto the surface of the hole transport layer. The deposition rate is 0.3~0.8 Å / s, and the vacuum level is 10. -5 ~10 -6 Pa, deposition thickness of 50~100 nm. The metal electrode is an Ag electrode.

[0038] Example 1 A room-temperature fabrication method for a perovskite solar cell based on modified tin dioxide, comprising the following steps: Step 1: Use a sheet resistance of 12 Ω / cm 2Using FTO conductive glass as a substrate, the FTO was cut into standard sizes and laser-etched. The substrate was then ultrasonically cleaned sequentially with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol for 15 minutes each, and dried with compressed air. Finally, it was treated with a UV-ozone cleaner for 18 minutes and set aside.

[0039] Dilute the SnO2 colloidal solution three times with deionized water. Weigh out... β -MHCl powder was added to the diluted SnO2 colloidal solution to a concentration of 0.5 mg / mL, and the mixture was stirred until homogeneous. The resulting... β A 3MHCl-SnO2 colloidal solution was spin-coated onto an FTO substrate at 3000 rpm for 30 s, followed by annealing at 150 °C for 30 min to obtain... β -MHCl-SnO2 electron transport layer.

[0040] Step 2: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO mixed solvent (volume ratio 4:1). Add 20 µL NMP as a coordinating additive and stir at room temperature for 12 h. Filter the perovskite precursor solution through a 0.22 µm PTFE filter. Apply the perovskite precursor solution using a one-step spin-coating method in a glove box. β Preparation of perovskite light-absorbing layer on MHCl-SnO2 electron transport layer: spin-coating at 1000 rpm for 10 s, then spin-coating at 4000 rpm for 30 s, adding 160 µL chlorobenzene as anti-solvent 28-30 s before the end of spin-coating, followed by annealing at 150℃ for 25 min.

[0041] Step 3: Dissolve Spiro-OMeTAD (90 mg) in 1 mL of chlorobenzene, add tBP (28.8 µL) and Li-TFSI acetonitrile solution (17.5 µL, concentration 520 mg / mL), and spin-coat the film in a glove box at a speed of 3000 rpm for 30 s.

[0042] Step 4: Deposit the Ag counter electrode using vacuum thermal evaporation at a deposition rate of 0.5 Å / s and a vacuum level of 10. -5 Pa, with a deposition thickness of 80 nm, yields a perovskite solar cell.

[0043] Example 2 A room-temperature fabrication method for a perovskite solar cell based on modified tin dioxide, comprising the following steps: Step 1: Use a sheet resistance of 12 Ω / cm2 Using FTO conductive glass as a substrate, the FTO was cut into standard sizes and laser-etched. The substrate was then ultrasonically cleaned sequentially with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol for 15 minutes each, and dried with compressed air. Finally, it was treated with a UV-ozone cleaner for 30 minutes and set aside.

[0044] Dilute the SnO2 colloidal solution three times with deionized water. Weigh out... β -MHCl powder was added to the diluted SnO2 colloidal solution to a concentration of 0.25 mg / mL, and the mixture was stirred until homogeneous. The resulting... β A 3MHCl-SnO2 colloidal solution was spin-coated onto an FTO substrate at 3000 rpm for 30 s, followed by annealing at 170 °C for 20 min to obtain... β -MHCl-SnO2 electron transport layer.

[0045] Step 2: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO mixed solvent (volume ratio 4:1). Add 20 µL NMP as a coordinating additive and stir at room temperature for 12 h. Filter the perovskite precursor solution through a 0.22 µm PTFE filter. Apply the perovskite precursor solution using a one-step spin-coating method in a glove box. β Preparation of perovskite light-absorbing layer on MHCl-SnO2 electron transport layer: spin-coating at 1000 rpm for 10 s, then spin-coating at 4000 rpm for 30 s, adding 160 µL chlorobenzene as anti-solvent 28-30 s before the end of spin-coating, followed by annealing at 140 ℃ for 30 min.

[0046] Step 3: Dissolve Spiro-OMeTAD (90 mg) in 1 mL of chlorobenzene, add tBP (28.8 µL) and Li-TFSI acetonitrile solution (17.5 µL, concentration 520 mg / mL), and spin-coat the film in a glove box at a speed of 3000 rpm for 30 s.

[0047] Step 4: Deposit Ag counter electrode using vacuum thermal evaporation at a deposition rate of 0.8 Å / s and a vacuum level of 10. -5 Pa, with a deposition thickness of 100 nm, yields a perovskite solar cell.

[0048] Example 3 A room-temperature fabrication method for a perovskite solar cell based on modified tin dioxide, comprising the following steps: Step 1: Use a sheet resistance of 12 Ω / cm 2 Using FTO conductive glass as a substrate, the FTO was cut into standard sizes and laser-etched. The substrate was then ultrasonically cleaned sequentially with glass cleaning fluid, deionized water, acetone, ethanol, and isopropanol for 15 minutes each, and dried with compressed air. Finally, it was treated with a UV-ozone cleaner for 10 minutes and set aside.

[0049] Dilute the SnO2 colloidal solution three times with deionized water. Weigh out... β -MHCl powder was added to the diluted SnO2 colloidal solution to a concentration of 0.75 mg / mL, and the mixture was stirred until homogeneous. The resulting... β A 3MHCl-SnO2 colloidal solution was spin-coated onto an FTO substrate at 4000 rpm for 20 s, followed by annealing at 130 °C for 40 min to obtain... β -MHCl-SnO2 electron transport layer.

[0050] Step 2: Weigh MAI (6.4 mg), FABr (13.5 mg), CsI (24.6 mg), PbBr2 (39.6 mg), FAI (190.4 mg), and PbI2 (591.2 mg) and dissolve them in 1 mL of DMF / DMSO mixed solvent (volume ratio 4:1). Add 20 µL NMP as a coordinating additive and stir at room temperature for 12 h. Filter the perovskite precursor solution through a 0.22 µm PTFE filter. Apply the perovskite precursor solution using a one-step spin-coating method in a glove box. β Preparation of perovskite light-absorbing layer on MHCl-SnO2 electron transport layer: spin-coating at 1000 rpm for 10 s, then spin-coating at 4000 rpm for 30 s, adding 160 µL chlorobenzene as anti-solvent 28-30 s before the end of spin-coating, followed by annealing at 160℃ for 20 min.

[0051] Step 3: Dissolve Spiro-OMeTAD (90 mg) in 1 mL of chlorobenzene, add tBP (28.8 µL) and Li-TFSI acetonitrile solution (17.5 µL, concentration 520 mg / mL), and spin-coat the film in a glove box at a speed of 3000 rpm for 30 s.

[0052] Step 4: Deposit the Ag counter electrode using vacuum thermal evaporation at a deposition rate of 0.3 Å / s and a vacuum level of 10. -6 Pa, with a deposition thickness of 50 nm, yields a perovskite solar cell.

[0053] Example 4 The other preparation processes in this embodiment are the same as in Example 1, except that in step 1, the SnO2 colloidal solution...β The concentration of -MHCl was 1.0 mg / mL.

[0054] Comparative Example 1 All other steps in this comparative example are the same as in Example 1, except that step 1 does not include... β -MHCl.

[0055] The performance of the perovskite solar cells obtained in the examples and comparative examples was tested, and the results are as follows: Figures 1-12 As shown.

[0056] Figure 1 The figures show the JV curves of the champion perovskite solar cells obtained in Example 1 and the comparative example of this invention. As can be seen from the figures, the perovskite solar cell obtained in Example 1 exhibits the best performance, with a champion photoelectric conversion efficiency (R) of PCE = 25.68%. V OC =1.173 V, J SC =26.36 mA / cm 2 The efficiency (FF) was 83.07%. Compared with Comparative Example 1, the performance of all parameters was significantly improved, and the hysteresis effect in both forward (F) and reverse (R) scans was significantly reduced. SnO2-R represents the reverse scan result of the champion photoelectric conversion efficiency of the perovskite solar cell obtained using SnO2 as the electron transport layer in the comparative example; SnO2-F represents the forward scan result of the champion photoelectric conversion efficiency of the perovskite solar cell obtained using SnO2 as the electron transport layer in the comparative example. β -MHCl-SnO2-R represents the reverse scan result of the champion photoelectric conversion efficiency of the perovskite solar cell obtained in Example 1; β -MHCl-SnO2-F represents the positive scan result of the champion photoelectric conversion efficiency of the perovskite solar cell obtained in Example 1.

[0057] Figure 2 The images show the FTIR characterization of the electron transport layer thin films obtained in step 1 of Embodiment 1 and Comparative Example 1 of this invention. As can be seen from the images, β The characteristic Sn-O-Sn peak in -MHCl-SnO2 starts from 561.1 cm⁻¹. -1 Moved to 588.3 cm -1 The Sn-OH peak is at 3350.9 cm⁻¹. -1 Moved to 3366.4 cm -1 Confirmed β A strong chemical interaction is formed between -MHCl and SnO2.

[0058] Figure 3The images show the XPS Sn 3d high-resolution spectra of the electron transport layer films obtained in step 1 of Embodiment 1 and Comparative Example 1 of this invention. As can be seen from the figures, β The Sn 3d peak of -MHCl-SnO2 shifts towards lower binding energies, which is attributed to the formation of Cl-Sn bonds.

[0059] Figure 4 The figures show the XPS O1s high-resolution spectra of the electron transport layer films obtained in step 1 of Example 1 and Comparative Example 1 of this invention. a represents Comparative Example 1, and b represents Example 1. As can be seen from the figures, the intensity ratio of lattice oxygen to hydroxyl peaks increased from 0.942 to 1.502, confirming the effective passivation of oxygen vacancy defects.

[0060] Figure 5 The contact angles of the perovskite precursor solution on the electron transport layer film surfaces obtained in step 1 of Example 1 and Comparative Example 1 are denoted as a, where a represents Comparative Example 1 and b represents Example 1. Figure 5 It can be seen that the perovskite precursor solution in β The contact angle of the -MHCl-SnO2 surface is only 7°, much smaller than the 32° on the pure SnO2 surface, confirming that... β -MHCl additives help improve the wettability of electron transport layer surfaces.

[0061] Figure 6 These are comparative images of the in-situ crystallization of the perovskite absorbing layer using fluorescence polarization microscopy (FPLM) in Example 1 and Comparative Example 1, respectively. a) is Comparative Example 1, and b) is Example 1. As can be seen from the images... β -MHCl modification significantly slows down the nucleation rate of perovskite, which is beneficial to grain growth.

[0062] Figure 7 This is a comparison of the steady-state PL spectrum and TRPL attenuation curve of the perovskite absorber layer in Example 1 and Comparative Example 1 of the present invention. a is the PL spectrum, and b is the TRPL attenuation curve. As can be seen from the figures... β -MHCl modification significantly improved the absorption intensity of perovskite films, from Figure 7 As can be seen from a, β The PL intensity of the -MHCl-SnO2-based perovskite film was significantly higher than that of the control sample, indicating that interfacial nonradiative recombination was effectively suppressed. Figure 7 As can be seen from b, β -MHCl-SnO2-based perovskite films carrier lifetime (τ) ave =1491.71 ns) is much longer than the control sample (τ ave =413.63 ns), which means β -MHCl modification can effectively repair perovskite interface defects and help suppress carrier nonradiative recombination.

[0063] Figure 8 These are scanning electron microscope (SEM) images comparing the surface and buried interface morphology of the perovskite light-absorbing layer in Example 1 and Comparative Example 1 of the present invention. a) is the SEM image of the surface of Comparative Example 1, b) is the SEM image of the surface of Example 1, c) is the SEM image of the buried interface of Comparative Example 1, and d) is the SEM image of the buried interface of Example 1. The average grain size of the perovskite increased from 950 nm to 1560 nm, and the defects at the buried interface were significantly reduced.

[0064] The device performance of the perovskite solar cells obtained in Example 1 and Comparative Example 1 was tested.

[0065] Figure 9 This is a comparison chart of the Mott-Schottky curves of the device in Embodiment 1 and the device in Comparative Example 1 of the present invention. As can be seen from the figure, β -MHCl-modified device built-in potential ( V bi =1.121 V) higher than the control device ( V bi =1.053 V), which means β -MHCl helps enhance the directional migration of charge carriers.

[0066] Figure 10 This is a comparison of the Nyquist impedance spectra of the device in Embodiment 1 and the device in Comparative Example 1 of the present invention. As can be seen from the figure, β -MHCl-modified devices exhibit lower charge transport resistance and higher recombination resistance. V OC The attenuation curves further confirm that nonradiative recombination was effectively suppressed.

[0067] Figure 11 This is a schematic diagram comparing the environmental stability of perovskite solar cells obtained in Example 1 and Comparative Example 1 of the present invention (the solar cells are not encapsulated). The test conditions were: storage in an atmospheric environment (25°C, relative humidity 30%~35%) for 5500 h. As can be seen from the figure, β The unencapsulated device modified with -MHCl retained 85.21% of its initial efficiency, while the control device retained only 34.71% after 3000 hours.

[0068] Figure 12 This figure shows the maximum power point tracking stability of the device in Embodiment 1 of the present invention. As can be seen from the figure, after 2000 hours of continuous illumination under a nitrogen atmosphere, β -MHCl-modified devices maintain an initial efficiency of over 97%.

[0069] The perovskite solar cell obtained by this invention comprises a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, a hole transport layer, and a metal counter electrode. The electron transport layer is formed by... β -MHCl modified SnO2 electron transport layer. β -MHCl is expressed through its thiol group (-SH) and amino group (-NH3). + The dual functional groups achieve multiple functions: (1) The -SH group acts as a reducing ligand, forming a strong coordination with the surface of SnO2 nanocolloids, effectively inhibiting the aggregation of nanoparticles, and at the same time chemically repairing oxygen vacancy defects in the SnO2 lattice; (2) The -NH3 group acts as a reducing ligand, forming a strong coordination with the surface of SnO2 nanocolloids, effectively inhibiting the aggregation of nanoparticles, and at the same time chemically repairing oxygen vacancy defects in the SnO2 lattice; + The groups form chemical bonds with the suspended hydroxyl groups on the SnO2 surface, further passivating the interface defect states; (3) β -MHCl acts as a "molecular bridge" connecting SnO2 to the perovskite layer: -NH3 + With halide ions (such as I) in perovskite precursors - Strong hydrogen bonds or electrostatic interactions are formed between the -SH group and Pb through Lewis acid-base interactions. 2+ Defect site coordination, this double anchoring effect not only significantly improves the wettability of the perovskite precursor solution on the SnO2 surface and effectively reduces the Gibbs free energy barrier for heterogeneous nucleation, but also moderately slows down the crystallization kinetics of perovskite, promotes full grain growth and preferred orientation, and ultimately obtains perovskite films with increased grain size, reduced grain boundaries, and significantly improved density and crystallinity.

[0070] The perovskite solar cell obtained by this invention has been tested and proven effective. β The Zeta potential of SnO2 colloids modified with -MHCl was significantly improved, the particle size distribution was more uniform, and they maintained good dispersion even after 30 days of storage; the conductivity of SnO2 films was significantly improved, and the ratio of lattice oxygen to hydroxyl peak intensity in the O 1s XPS spectrum (I O 2- / I OH - The value increased from 0.942 to 1.502, confirming the effective passivation of oxygen vacancy defects. β -MHCl modification significantly reduced the contact angle of the perovskite precursor solution on the SnO2 surface from 32° to 7°, effectively lowering the Gibbs free energy barrier for heterogeneous nucleation. DFT calculations showed that Cl substitution of surface hydroxyl groups reduced the SnO2(110) surface free energy from 0.3067 J / m² to 0.2948 J / m². 2 The H2O adsorption energy increased from -1.482 eV to -1.649 eV; the surface free energy of oxygen vacancies decreased from 1.6332 J / m after Cl passivation to 1.5336 J / m. 2Thanks to the precise control of crystallization kinetics, the average grain size of the perovskite film increased from 950 nm to 1560 nm, the buried interface defects were significantly reduced, and the carrier lifetime was greatly improved from 413.63 ns to 1491.71 ns.

[0071] The champion achieves a photoelectric conversion efficiency of 25.68% (open circuit voltage). V OC =1.173 V, short-circuit current J SC =26.36 mA / cm 2 With a fill factor of FF = 83.07%, this is one of the highest efficiencies reported for nip-type perovskite solar cells fabricated under atmospheric conditions. Compared to the unmodified control device (PCE = 21.21%), the efficiency is improved by 21%. Simultaneously, the hysteresis index is significantly reduced from 15.55% to 7.05%. The unencapsulated device exhibits excellent long-term stability: after 5500 h of storage in an atmospheric environment (25°C, relative humidity 30%~35%), it retains 85.21% of its initial efficiency; after 2000 h of continuous illumination at maximum power point under nitrogen atmosphere, it retains over 97% of its initial efficiency, significantly better than the unmodified control device (which retains only 34.71% after 3000 h).

[0072] This invention is achieved through β The buried interface modification strategy of -MHCl pre-embedded SnO2 electron transport layer has successfully achieved the fabrication of high-efficiency and stable perovskite solar cells under atmospheric conditions. This strategy simultaneously solves three core problems: SnO2 defect passivation, precursor wettability improvement, and perovskite crystallization kinetics regulation, providing a practical technical path for the industrialization of perovskite photovoltaic technology.

Claims

1. A perovskite solar cell based on modified tin dioxide, characterized in that, It includes, from bottom to top, a conductive substrate, an electron transport layer, a perovskite light-absorbing layer, and a hole transport layer; it also includes a metal counter electrode; The electron transport layer is mercaptoethylamine hydrochloride. β Preparation of SnO2 modified with -MHCl.

2. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide as described in claim 1, characterized in that, Includes the following steps: Step 1: Spin-coating a conductive substrate surface with... β SnO2 colloid of -MHCl was annealed to obtain an electron transport layer. Step 2: Prepare a perovskite light-absorbing layer on the electron transport layer using spin coating, followed by annealing. Step 3: Spin-coat a hole transport layer onto the surface of the perovskite light-absorbing layer obtained in Step 2; Step 4: Deposit a metal counter electrode on the surface of the hole transport layer.

3. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, SnO2 colloidal solution β The concentration of -MHCl is 0.25~1.0 mg / mL.

4. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, In step 1, the annealing temperature is 130~170 ℃ and the annealing time is 20~40 min.

5. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, In step 2, the perovskite light-absorbing layer is FA. 0.9 Cs 0.07 MA 0.03 PbI 2.76 Br 0.24 .

6. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, The spin coating process of the perovskite light-absorbing layer in step 2 is as follows: first spin coating at 1000 rpm for 10 s, and then spin coating at 4000 rpm for 30 s.

7. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, In step 2, the annealing temperature is 140~160 ℃ and the annealing time is 20~30 min.

8. The room-temperature fabrication method of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, In step 2, chlorobenzene is added as an anti-solvent during spin coating.

9. A method for room-temperature fabrication of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, The conductive substrate is fluorine-doped tin oxide (FTO) conductive glass; the hole transport layer is 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirodifluorene.

10. A method for room-temperature fabrication of a perovskite solar cell based on modified tin dioxide according to claim 2, characterized in that, In step 4, the vacuum evaporation rate is 0.3~0.8 Å / s, and the vacuum degree is 10. -5 ~10 -6 Pa, with a deposition thickness of 50~100 nm.